2016
DOI: 10.1073/pnas.1608979113
|View full text |Cite
|
Sign up to set email alerts
|

Birth of a W sex chromosome by horizontal transfer ofWolbachiabacterial symbiont genome

Abstract: Sex determination is a fundamental developmental pathway governing male and female differentiation, with profound implications for morphology, reproductive strategies, and behavior. In animals, sex differences between males and females are generally determined by genetic factors carried by sex chromosomes. Sex chromosomes are remarkably variable in origin and can differ even between closely related species, indicating that transitions occur frequently and independently in different groups of organisms. The evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 47 publications
5
121
0
3
Order By: Relevance
“…Endosymbionts can have a similar impact, as illustrated by the Wolbachia feminizing element in populations of woodlice (Cordaux, Bouchon, & Grève, ). Increasing numbers of theoretical models outline the scenarios in which we might expect sex ratio selection to drive the evolution of new sex chromosome systems (Kozielska, Weissing, Beukeboom, & Pen, ; Úbeda, Patten, & Wild, ) and there is growing support from a few taxa (Badawi, Moumen, Giraud, Grève, & Cordaux, ; Becking et al, ; Chebbi et al, ; Cordaux et al, ; Cordaux & Gilbert, ; Leclercq et al, ; Miura, ). Similarly, a recent study outlined the role of haploid selection via gametic competition and meiotic drive in increasing the lability of sex determination systems (Scott et al, ).…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
“…Endosymbionts can have a similar impact, as illustrated by the Wolbachia feminizing element in populations of woodlice (Cordaux, Bouchon, & Grève, ). Increasing numbers of theoretical models outline the scenarios in which we might expect sex ratio selection to drive the evolution of new sex chromosome systems (Kozielska, Weissing, Beukeboom, & Pen, ; Úbeda, Patten, & Wild, ) and there is growing support from a few taxa (Badawi, Moumen, Giraud, Grève, & Cordaux, ; Becking et al, ; Chebbi et al, ; Cordaux et al, ; Cordaux & Gilbert, ; Leclercq et al, ; Miura, ). Similarly, a recent study outlined the role of haploid selection via gametic competition and meiotic drive in increasing the lability of sex determination systems (Scott et al, ).…”
Section: Future Directions and Perspectivesmentioning
confidence: 99%
“…Sex chromosomes are the product of recombination suppression between the X and Y (or Z and W) chromosomes 65 , and there is increasing evidence that this process occurs in order to resolve sexual conflict 27,[66][67][68] . Data from studies in guppies (Poecilia reticulata) 27 and sticklebacks 66 are consistent with the theoretical prediction that recombination between the X and Y chromosomes is selected against in order to maintain male-benefit alleles on the Y chromosome [69][70][71][72] , thereby limiting their inheritance to males.…”
Section: Feedback Loops On Sex Chromosomesmentioning
confidence: 99%
“…Although the Wolbachia-derived gene(s) that became sex-determining gene(s) remain to be identified among many possible candidates, the genomic and genetic evidence are clear that this Wolbachia insertion is determining sex in this pillbug strain. Leclerq et al [5] also found that although this insertion is quite recent, many structural changes (rearrangements, duplications) have occurred compared to the wVulC genome, which study will probably help understand which bacterial gene(s) have retained a function in the nucleus of the pillbug. Also, in the future, it will be interesting to understand how and why exactly the nuclear inserted Wolbachia rose in frequency in the pillbug population and how the cytoplasmic Wolbachia was lost, and to tease apart the roles of selection and drift in this event.…”
mentioning
confidence: 97%
“…Several models have been developed to explain this pattern but empirical data are lacking and the causes of the fast sex chromosome turn over remain mysterious [2][3][4]. Leclerq et al [5] in a paper that just came out in PNAS have focused on one possible explanation: Wolbachia. This widespread intracellular symbiont of arthropods can manipulate its host reproduction in a number of ways, often by biasing the allocation of resources toward females, the transmitting sex.…”
mentioning
confidence: 99%
See 1 more Smart Citation